1991
DOI: 10.1161/01.cir.83.3.886
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic body surface potential mapping in the Wolff-Parkinson-White syndrome. Noninvasive determination of the ventricular insertion sites of accessory atrioventricular connections.

Abstract: The following conclusions were drawn: 1) BSPM using QRS analysis accurately predicts the ventricular insertion site of accessory AV connections in the presence of a delta wave in the electrocardiogram; 2) the ventricular insertion sites of accessory AV connections determined by BSPM and by EPS at surgery were identical or within one mapping site (1.5 cm or less) in all but four of 18 cases; three of the four exceptions had more than one accessory AV connection, and the other had a very broad ventricular insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…[1][2][3] Our group has participated in this process as well. [4][5][6][7] The aim of the current study was to test the hypothesis that noninvasive epicardial activation mapping is a valid method to provide activation sequences in patients with atrial and ventricular rhythm disorders.…”
Section: Clinical Perspective On P 75mentioning
confidence: 99%
“…[1][2][3] Our group has participated in this process as well. [4][5][6][7] The aim of the current study was to test the hypothesis that noninvasive epicardial activation mapping is a valid method to provide activation sequences in patients with atrial and ventricular rhythm disorders.…”
Section: Clinical Perspective On P 75mentioning
confidence: 99%
“…Epicardial right ventricular breakthrough (RVBT) is indicative of conduction via the AV node and the Purkinje system. Studies by Liebman et al (15) have shown evidence of lack of epicardial RVBT for WPW right-sided and anteroseptal pathways. This may be explained by the proximity of the AP to the right bundle branch.…”
Section: Discussionmentioning
confidence: 99%
“…This method can provide valuable information on such conditions as congenital heart disease,7) right ventricular hypertrophy,8,9) cardiomyopathy,10-12) ventricular conduction disturbances13,14) and arrhythmias. [15][16][17][18][19][20][21] This method has also proved to be particularly useful in the assessment of myocardial infarction in terms of diagnosis,22-27) local_ ization,27-32) complications,) prognosis) and assessment of therapy.38-40) Furthermore, exercise BSPM is one of the promising methods for the detection, localization and evaluation of myocardial ischemia. [41][42][43] Although the potential utility of the BSPM is promising, the clinical data available at this time are still not sufficient to establish perfect diagnostic standards, and a normal data base of the BSPM remains to be established.…”
Section: Discussionmentioning
confidence: 99%